THE PATH TO SELF-DEFINITION: THE CONSTRUCTION OF WOMEN’S EXISTENCE IN MUḤAMMAD JIBRĪL’S SIKKAT AL-MANĀṢIRAH - Nur Desyanti Sukisman (CMES (Center of Middle Eastern Studies), 2026)
This research focuses on the analysis of women’s existence in the Egyptian novel entitled Sikkat al-Manāṣirah by Muḥammad Jibrīl. This study aims to reveal the strategies and driving factors of the main female character in fighting for her existence in the novel. The primary data of this study are derived from Sikkat al-Manāṣirah, while the secondary data are obtained from books, previous studies, and relevant online references. This study uses qualitative descriptive methods and library techniques, namely by describing data related to the criteria of strategies and driving factors of the struggle for women’s existence using Simone de Beauvoir’s existentialist feminism approach. The results of the study show that there are four strategies of the main female character in fighting for her existence, including being an intellectual woman, a hardworking woman, contributing to society, and refusing to be an object. Meanwhile, the driving factors for the emergence of women’s struggle for existence are triggered by economic conditions and thoughts towards change. The implication of this research confirm that women’s existence within the text functions as a process of becoming a subject through choice, labor, and self-assertion. These findings strengthen gender-sensitive literary through economic independence and critical consciousness.